Foundational and Practical Aspects of Resource Analysis First International Workshop, FOPARA 2009, Eindhoven, The Netherlands, November 6, 2009, Revised Selected Papers - Eekelen, Marko; Shkaravska, Olha.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the First International Workshop on Foundational and Practical Aspects of Resource Analysis, FOPARA 2009, held at the 16th International Symposium on Formal Methods, FM 2009, in Eindhoven, The Netherlands, in November 2009. The 10 revised full papers were carefully reviewed and selected from 13 research presentation contributions and one invited lecture.
FOPARA 2009 -- Comparing Cost Functions in Resource Analysis -- Improvements to a Resource Analysis for Hume -- A Space Consumption Analysis by Abstract Interpretation -- Global and Local Space Properties of Stream Programs -- Characterising Effective Resource Analyses for Parallel and Distributed Coordination -- Static Complexity Analysis of Higher Order Programs -- Derivational Complexity Is an Invariant Cost Model -- A Local Criterion for Polynomial-Time Stratified Computations -- Non-deterministic Boolean Proof Nets -- Polynomial Time Computation in the Context of Recursive Analysis.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Programming Techniques